The donor footprint and gender gaps - Maria Perrotta Berlin; Evelina Bonnier; Anders Olofsgård (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In this paper we analyse the impact of foreign aid on gender outcomes and attitudes. We do this by matching geocoded household surveys with aid projects. This offers a middle way between project evaluations and aggregated cross-country comparisons, measuring an average community effect around projects. We find increased opportunities for women to work outside the household, which could strengthen their bargaining power. However, we find mixed results in terms of the impact on women's control over other key areas of their lives. We argue this is related to differences in what is required for change to happen at the community level.
Keywords: P45; O12; O19; J16; C55; 330; foreign aid; gender; development; geocoded data; matching; impact analysis